ANALISIS RESPON MAHASISWA PENDIDIKAN FISIKA TERHADAP COMPUTER BASED TESTING PADA MATA KULIAH MANAJEMEN LAB - Firdha Kusuma Ayu Anggraeni; Lailatul Nuraini (Universitas Jember, 2020)
Abstract: The using of technology in the field of education especially in college is the using of e-learning. E-learning is a way of teaching and learning activities assisted by information and communication technology. One example of e-learning implementation is test. This type of exam is referred to as an online test or computer based testing (CBT). University of Jember has an e-learning called Media Manajemen Pembelajaran (MMP) and one of the features in it is a quiz feature that can be used by lecturers in giving quizzes, tests, or examinations to students. . The research that has been carried out aims to determine the response of Physics Education students to the implementation of online examinations in Lab Management courses. The question model used in this exam is in the form of multiple choices. After students finish working on the questions, students fill in the questionnaire responses which are then processed and presented in tabular forms, then analyzed descriptively. The results obtained from this study give good results. Students give positive responses to representations about using the online system for exams, the interest of students in taking online exams, easy use of web access, online system test displays and questions, and responses to the methods used in the online system. Keywords: guided inquiry, decision making, physics learning.